Operations research :Theory and applications - Sharma, J.K. (India: Macmillan India, 2013)
Operations Research is the application of mathematical principles in decision making. This method uses techniques like statistical analysis and mathematical modeling to find the optimal solution to a problem or a situation. Operations Research: Theory And Applications covers the various techniques and principles used in operations research. It discusses concepts like Linear, Non-Linear, and Goal Programming, Decision Theory, Markov Chains, Information Theory, Theory of Games, and Classical Optimization Methods. The book provides clear and concise concept explanations. They are further clarified through the use of many illustrative examples. Most of the chapters also have Management Cases to help students understand how the concepts are applied in real business situations. In this fifth edition of the book, most of the chapters have been revised or reorganized to make the text even more useful and comprehensible to students. The book helps students clearly understand the processes involved in problem solving. It provides a comprehensive coverage of model formulation methods, solution procedures and analysis of results. Operations Research: Theory And Applications is designed as a core academic material for courses like MBA, CA, ICWA, MCA, BE, BTech and MSc. The book defines the fundamental principles of operations research and shows how they are applied in solving business problems. All chapters start with sections providing a Preview and outlining the Learning Objectives. These help the students understand what will be covered in that chapter and helps them stay focused. The Concept Quizzes in each chapter reinforces the principles and applications of the operations research techniques discussed in the chapter. The book helps students clearly understand the processes involved in problem solving. It provides a comprehensive coverage of model formulation methods, solution procedures and analysis of results.
Appendix A-B 918-937p.; Selected references 939-940p.; Index 941-944p.
Keywords: Assignment problem; Gaol programming; Quening theory; Iinear programming